Audio and video editing system design based on OpenCV - Юэханг Сонг; Борун Чен; Сяобинь Лю; Ху Вэйцзюнь; Се Сяньюй; Янь Юци (Информатика. Экономика. Управление, 2022)
With the rapid development of the Internet, a new carrier for people to perceive the world and communicate with each other - audio and video - is gradually being favoured by the public. The development of multimedia technology and artificial intelligence technology has provided a milestone for the maturity of audio and video technology. In particular, short video platforms have slowly become a new network position for various media promotions. Especially at the moment of the epidemic, the channel of understanding the world through audio and video is increasingly valued. The public has put forward higher demands on the content and presentation of audio and video. Therefore, it is particularly important to produce quality audio-video that meets the requirements of the times, which cannot be achieved without a feasible audio-video editing system. In addition, after previous research and practice, the application of artificial intelligence technology in the field of imaging has also become mature, including some applications in the direction of entertainment. Applying AI technology to the video editing process can improve the efficiency of video editing, increase the interest of video content, and allow video creators to focus on content creation without spending too much time and energy on video editing operations, thus creating better quality videos. This design is the main technology of OpenCV and front-end technology stack, such as JavaScript, React and Electron, to implement basic video editing, video filters, in addition to the development of a friendly interactive interface. The implementation of basic video editing module and video filter module are both based on OpenCV implementation. In this design, the basic video editing implements pan, zoom and rotate operations on the video, and the video filter module is implemented by changing the RGB channel values of the image. The operations on the video can be broken down into operations on each frame of the video, and OpenCV provides a way to implement these operations. The paper concludes with a summary of the shortcomings and flaws in the design, and an outlook on the next steps and future directions.